ANALYSIS CONTENT OF TRACEELEMENTS IN TABULAR WATERS KRASNOKUTSK FIELD - Бандуріна O. В. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Analyzed the content of trace elements iodine, bromine tabular waters Krasnokutsk field. Deposits studied field with a high content of iodine and bromine ions. The relation between high iodine content in groundwater and oilfield related thermobaric conditions. Keywords: trace element, iodine, bromine, tabular water, oil pools, thermobaric conditions.